Introducing the Bonn Experiment System (BoXS) - Mirko Seithe (University of Bonn, Bonn Graduate School of Economics (BGSE), 2012)
Computerised experiments play a vital part in the modern economic and social sciences. As the technology advances, more complex and sophisticated experiments become feasible. Fast internet connections are widely available today and mobile devices have become capable of running complex graphical applications. The Bonn Experiment System (BoXS) was designed to provide a platform for designing and conducting computerised experiments which is both easy to approach and use, as well as flexible in its possible applications. It does not require installation and uses a lean client which runs on Windows, MacOS and Linux and only requires a web browser and a Java Runtime Environment to execute. This paper intends to highlight the main features and limitations of the BoXS and provide some guidance for experimenters getting started with it. It also discusses some of the design decisions and provides in-depth information on technical aspects of the system. The appendix includes both the documentation and full code examples.
Keywords: C88; C99; 330; Experiment System; Software; Experiment Conduction; Java